Entrepreneurship Education and Students Entrepreneurial Intention: Does Teacher Creativity Really Matter? - Karuniana Dianta Arfiando Sebayang; Agus Wibowo; Muhammad Hakimi Mohd Shafiai; Kardoyo Kardoyo (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
Escalating entrepreneurs is expected to provide more job opportunities that contributes in diminishing social and economic issues. This study aims to analyze the interconnectedness between teacher creativity and entrepreneurial intention as well as investigate the role of entrepreneurship education. This research adopted a descriptive correlational study that aims to analyze the nexus between variables using a quantitative approach study. This current study engaged primary data from an online questionnaire that was performed online to vocational students with five Likert scale choices. Furthermore, the statistical analysis was conducted using partial least squares-structural equation modeling (PLS-SEM) with the use of SmartPLS 3.0 software. The outcomes of this study indicate that teacher creativity takes a crucial role in determining students’ intention of being entrepreneurs. These results imply that teachers’ creativity in classroom learning to inspire, motivate, and encourage students can support entrepreneurship education as well as students’ entrepreneurial intention. The basic rationale is that entrepreneurship education is subjected to several aspects including cognitive, affective and psychomotor. Keywords: Entrepreneurship education, Entrepreneurial intention, Students’ intention, Teacher’s creativity